Perancangan Bisnis Untuk Produk Manisan Asam Patimang - Meidysari Pratama Chandra; Ellen Saputra (Universitas Ciputra Surabaya, 2017)
This research was done to know what people think about Patimang tamarind candy business idea and to research what kind of tamarind candy that they want. Patimang tamarind candy is one kind of healthy snacks that are rarely considered by the people nowadays because the rise of modern snacks that are not good for health and the design that was old. Besides, the author want to change the design concept to be more modern. The research was conducted using quantitative and qualitative methods. The quantitative method using quistionnaire which is distributed to men and woman aged 20-40 years who lived in Surabaya. While the qualitative method by interview to the potential market and literature study. The result of the research shows that most of the correspondents like Patimang tamarind candy and willing to change their snacks to the healthier Patimang tamarind candy. Furthermore, the shape, taste and effective packaging need to be changed so the product look attractive , as well as its identity and design should be modern. Media marketing is done by using direct selling and through social media